Relationship between emotional regulation and anxiety among nurses during the Covid-19 pandemic - Anisa Oktiawati; Khodijah Khodijah; Arif Rakhman (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2022)
Background: The Coronavirus Disease (COVID-19) outbreak occurred in almost all of countries. This phenomenon causes changes in various aspects of life, such as health, economic, social, psychological, cultural, and more. Psychological responses experienced by health workers are the feelings of anxiety about their health and the spread of the virus to their families. Hence, nurses need to understand the problems that being faced, therefore they have no difficulties in recognizing their emotions. The ability of nurses to regulate their emotions is needed to focus on dealing with a problem.Objectives: This study aims to determine the relationship between emotional regulation and anxiety among nurses during the COVID-19 pandemic. Methods: This is quantitative research with a descriptive correlation design and a cross sectional approach. The sampling technique that used was accidental sampling with a total of 202 respondents, which was carried out during July 2020. Respondents filled out questionnaires that given by the researcher trough online google form. The research instruments used were Emotion Regulation Questionnaire (ERQ) and anxiety questionnaire with Coronavirus Anxiety Scale (CAS)Results: The results of the pearson product moment analysis obtained that p-value is 0.007 < 0.05. It can be concluded that there is a relationship between emotional regulation and anxiety among nurses during the COVID-19 pandemic.Conclusions : Nurses who have good emotional regulation skills will not experience anxiety during the COVID-19 pandemic. Nurses are expected to be able to control their emotions, so they can recognize problems and determine appropriate actions, so that anxiety does not occur.